Improvement of organizational and technological decisions of building production and remote control of construction projects using UAV - Zeltser, Robert; Kolot, Maksim; Panasyuk, Ivan (Ways to Improve Construction Efficiency, 2019)
The article highlights the issues of improving organizational and technological solutions for the construction industry, presents data on the experience of using unmanned aerial vehicles and special software for organizing remote monitoring of construction projects in Ukraine. The experience of using UAVs in addressing such issues as the management’s lack of relevant information on state of affairs at construction site, late identification of actual deviations from the project documentation, uncontrolled influence of human factor in the process of checking the volume and quality of work performed by contractors, and insufficient communication between project participants. It was concluded that drones are an effective tool that has a wide scope of application at the stages of survey and design works, zero-cycle works, construction of the above-ground part of buildings and further control of the technical condition of buildings during operation.